2004
DOI: 10.1111/j.1365-2648.2004.03010.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of guidelines to avoid and report exposure to blood and body fluids

Abstract: The findings suggest that strategies must be developed to improve compliance with universal precautions and reporting guidelines by all health care professionals. The extent of, and reasons for, non-compliance with both local and national guidelines remain relatively unexplored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 41 publications
5
74
1
1
Order By: Relevance
“…Although the use of individual protection equipment does not keep the worker from having an accident, it does help to reduce the exposure to risk (12) . The investigation showed that the reality of complying with precaution measures is far from being that which is recommended (13)(14) .…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of individual protection equipment does not keep the worker from having an accident, it does help to reduce the exposure to risk (12) . The investigation showed that the reality of complying with precaution measures is far from being that which is recommended (13)(14) .…”
Section: Discussionmentioning
confidence: 99%
“…Ces facteurs peuvent être associés à l'organisation des établissements de santé, aux ressources nécessaires pour la mise en oeuvre des PS (26), comme ils peuvent être liés au manque d'hygiénistes selon une étude réalisée au nord de l'Inde (27). Au Pays de Galles, 63,3 % ont admis des jugements relatifs à la nationalité, au mode de vie ou à l'orientation sexuelle des patients sur le port des protections individuelles (28). D'autre part, Ferguson et al en 2004 ont révélé que la non-disponibilité du matériel (7 %) et la non-efficacité de ce matériel (3 %) ont été des facteurs liés à la non-application des PS (29).…”
Section: Maîtrise Du Port De Gants à Usage Uniqueunclassified
“…Non-compliance among health care workers could also be due to their belief that their workload is increased by adhering to universal precautions and therefore, these procedures are difficult to accommodate due to day to day current clinical pressures [35]. Other reasons include perceived reduction in dexterity when wearing gloves, and the absence of penalties [36].…”
Section: Discussionmentioning
confidence: 99%